A survey of treatment practices for febrile illnesses among traditional healers in the Nigerian middle belt zone (2005)
This survey was conducted to investigate the pattern of treatment practices for febrile illnesses among one hundred and eighty five traditional healers from the Nigerian Middle belt zone ethnomedicine. Data collection was through use of the semi structure questionnaire administered by trained interviewers recruited from the study sites – Gboko and Katsina Ala Local Government Areas. A total of 176 (95.1%) reportedly diagnosed through the presenting complaints and symptoms and 3 (1.6%) made diagnoses through divination. All the respondents indicated their referral practices, with 100 (54.1 %) of the respondents reported that they had once referred clients. Respondents listed 164 plants used in the preparation of the various treatment modalities. Institution of treatment follows this diagnostic practice. Treatment of different febrile illnesses involve the use of 338 liquid herbs, powdered herbs, medicinal scarifications, incantations and sacrifices which suggests the confidence this group has in the efficacy of their herbs for treating febrile illnesses. An appreciable level of referral 54.1% practice was also found among the traditional healers. The findings of this study strengthen the need to recognize the traditional health practitioners in the treatment of health problems especially febrile illnesses, and to establish quality control mechanism in partnership with them to improve their treatment practices.